THE EFFECT OF DRY SLUDGE PRODUCTS FROM CLEAN WATER TREATMENT ON GROWTH AND YIELD OF RADISH ON PEAT SOIL - Sagita, Devia Rahma; Susana, Rini; Darussalam, Darussalam (Jurnal Sains Mahasiswa Pertanian, 2019)
Peat soil has a very low pH so it is unsuitable to be used as a planting medium. Efforts to increase the pH of peat soils can be through the provision of dry sludge resulting from clean water treatment. This study shows to determine the effect of dry sludge clean water treatment on the growth and yield of radish on peat soil, knowing the best dose of dry sludge for the growth and yield of radish on peat soil and to determine the Pb content in white radish plants. This research was carried out in the experimental garden of the Faculty of Agriculture, Tanjungpura University, Pontianak. This study used a Completely Randomized Design (CRD), which consisted of 5 treatments and 4 replications, each treatment consisting of 3 samples, so that there were 60 plants. The treatment in question is: p1 = 15% dry sludge equivalent to 1,2 kg/polybag, p2 = 30% dry sludge equivalent to 2,4 kg/polybag, p3 = 45% dry sludge equivalent to 3,6 kg/polybag, p4 = 60% dry sludge equivalent to 4.8 kg/polybag, p5 = 60% dry sludge equivalent to 6 kg/polybag. Variables observed were the number of leaves, the wet weight of the upper part of the plant, the dry weight of the upper part of the plant, the wet weight of tubers, the dry weight of tubers, the length of tubers, the diameter of tubers, the content of Pb at the top and radish tuber. The result of this study indicate that the dose of dry sludge resulting from clean water treatment can increase the wet weight of white radish tuber. This study did not get the best dose of dry sludge for growth and yield of white radish, but a 45% dose was an effective dose to produce growth dan yield of better white radish. Pb content in the upper part of the plant is below the maximum threshold, while the Pb content in white radish tuber is above the maximum threshold allowed according to SNI 7378-2009.Â Â Keywords: dry sludge from the treatment of clean water, radish, peat soil